Physician-assisted death: A Canada-wide survey of ALS health care providers - Abrahao, Agessandro [UNIFESP] (2016)
Objective:To survey amyotrophic lateral sclerosis (ALS) health care providers to determine attitudes regarding physician-assisted death (PAD) after the Supreme Court of Canada (SCC) invalidated the Criminal Code provisions that prohibit PAD in February 2015.Methods:We conducted a Canada-wide survey of physicians and allied health professionals (AHP) involved in the care of patients with ALS on their opinions regarding (1) the SCC ruling, (2) their willingness to participate in PAD, and (3) the PAD implementation process for patients with ALS.Results:We received 231 responses from ALS health care providers representing all 15 academic ALS centers in Canada, with an overall response rate for invited participants of 74%. The majority of physicians and AHP agreed with the SCC ruling and believed that patients with moderate and severe stage ALS should have access to PAD